Natuna Waters: Explaining a Flashpoint between Indonesia and China - Agusman, Damos Dumoli (UI Scholars Hub, 2023)
Abstract The Natuna waters have recently been a flashpoint between China and Indonesia as a result of China's vague claim of a nine dash line (9DL). It has caused a number of incidents and standoffs between legal enforcement agencies of both countries and sparked a diplomatic row. This article explores how the ambiguous claim of a historic right/9DL was gradually introduced by China and then coercively applied in the Natuna waters. It also attempts to identify what China actually claims in the waters. It will then examine how Indonesia under the Jokowi administration responds to the claims, and elaborate what measures Indonesia has taken and will continue to take in order to protect its maritime interests against China’s 9DL claim. It concludes that Indonesia regards China’s illegal claim as a matter of principle and thus takes an uncompromising stand.